2021
DOI: 10.3390/cancers13225847
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Targeted Therapies beyond BRAF-Mutant Melanoma: Potential Druggable Mutations and Novel Treatment Approaches

Abstract: Melanomas exhibit the highest rate of somatic mutations among all different types of cancers (with the exception of BCC and SCC). The accumulation of a multimode of mutations in the driver oncogenes are responsible for the proliferative, invasive, and aggressive nature of melanomas. High-resolution and high-throughput technology has led to the identification of distinct mutational signatures and their downstream alterations in several key pathways that contribute to melanomagenesis. This has enabled the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 192 publications
(239 reference statements)
1
21
0
Order By: Relevance
“…Case 2 is unique in several ways. Currently, only 30% of relapsed-refractory melanomas respond to KIT inhibitors ( 1 ). This case is in concordance with a prior case report demonstrating a possible role for ctDNA in monitoring KIT -mutant melanoma response to treatment ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case 2 is unique in several ways. Currently, only 30% of relapsed-refractory melanomas respond to KIT inhibitors ( 1 ). This case is in concordance with a prior case report demonstrating a possible role for ctDNA in monitoring KIT -mutant melanoma response to treatment ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma is the deadliest form of skin cancer, with an incidence that has continued to increase over the past several decades ( 1 ). The introduction of novel treatments, however, has contributed to the substantial improvement in patient outcomes, with an approximately 5% decline in the mortality rate since 2013 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The contemporaneous emergence of next-generation sequencing has improved our abilities to characterize individual patients’ melanomas and to research potential genetic targets. NRAS mutations are present in approximately 20% of all melanomas and portend a worse prognosis than does NRAS -wildtype status ( 8 , 9 ). Although the lack of effective targeted therapy makes NRAS -mutant melanoma a more controversial subtype than BRAF -mutant melanoma, studies suggest that NRAS mutational status is an independent prognostic factor for metastatic melanoma and may be associated with immunotherapy response ( 9 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…NRAS mutations are present in approximately 20% of all melanomas and portend a worse prognosis than does NRAS -wildtype status ( 8 , 9 ). Although the lack of effective targeted therapy makes NRAS -mutant melanoma a more controversial subtype than BRAF -mutant melanoma, studies suggest that NRAS mutational status is an independent prognostic factor for metastatic melanoma and may be associated with immunotherapy response ( 9 15 ). Immunotherapy is considered the standard of care for most patients with locally advanced or metastatic melanoma without a contraindication, but their comparative efficacy in NRAS -mutant versus NRAS -wildtype melanoma remains unclear ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence has increased steadily and significantly in recent years, primarily among white populations [ 6 ]. According to the International Agency for Research on Cancer (IARC), 324,635 new melanoma cases and 57,043 patient deaths were reported in 2020 [ 1 , 8 ]. When diagnosed at early stages, melanoma has a 5-year survival rate higher than 90%, and it can be successfully treated with surgery alone [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%